Genotype–phenotype specificity in Menke–Hennekam syndrome caused by missense variants in exon 30 or 31 of CREBBP. Issue 6 (20th March 2019) - Banka, Siddharth; Sayer, Rebecca; Breen, Catherine; Barton, Stephanie; Pavaine, Julija; Sheppard, Sarah E.; Bedoukian, Emma; Skraban, Cara; Cuddapah, Vishnu A; Clayton‐Smith, Jill
Abstract : CREBBP loss‐of function variants cause Rubinstein–Taybi syndrome (RTS). There have been two separate reports of patients with missense variants in exon 30 or 31 of CREBBP in individuals lacking the characteristic facial and limb dysmorphism associated with RTS. Frequent features in this condition include variable intellectual disability, short stature, autistic behavior, microcephaly, feeding problems, epilepsy, recurrent upper airway infections, and mild hearing impairment. We report three further patients with de novo exon 31 CREBBP missense variants. The first individual has a c.5357G>A p. (Arg1786His) variant affecting the same codon as one of the previously described patients. Both these patients could be recognized by clinicians as mild RTS. Our second patient has a c.5602C>T p.(Arg1868Trp) variant that has been described in five other individuals who all share a strikingly similar phenotype. The third individual has a novel c.5354G>A p.(Cys1785Try) variant. Our reports expand the clinical spectrum to include ventriculomegaly, absent corpus callosum, staphyloma, cochlear malformations, and exomphalos. These additional cases also help to establish genotype–phenotype correlations in this disorder. After the first and last authors of the previous two reports, we propose to call this disorder "Menke–Hennekam syndrome" to establish it as a clinical entity distinct from RTS and to provide a satisfactory name for adoption by parents and professionals, thus facilitating appropriate clinical management and research.